Methodik für Wissens- und Prozessmanagement bei der interaktiven kollaborativen Montage variantenreicher Produkte - Schneider, Marcus (Reihe Informationsmanagement im Engineering Karlsruhe, 2021)
Collaboration-oriented knowledge and process management must support the integration of all systems involved, address specific questions of the division of labor within the control system, but also enable the planning and engineering of new variants and contribute to a continuous increase in quality through the persistence and analysis of process data.